Pemanfaatan Lorong Baca di MI Muhammadiyah Karanglo dan MI Ma’arif NU 1 Pageraji - Tiwan, Tiwan; Bambang Suharto, Abdul Wachid (J-PGMI: Jurnal Pendidikan Guru MI, 2022)
Interest in reading students in Indonesia is still low. Serious efforts are needed to increase reading interest. The purpose of this study was to describe the use of reading passages at MI Muhammadiyah Karanglo and MI Ma'arif NU 1 Pageraji located in Cilongok District, Banyumas Regency. This study uses field research qualitatively, with observations, interviews, document studies as data collection techniques. Data analysis was carried out using interactive techniques, namely data reduction, data presentation, and concluding. Based on the results of collecting data and information from the field, a description of the reading hallway that uses the classroom terrace as a place to read for students is obtained. Reading aisles can bring reading material closer to the reach of students, so it can increase students' reading interest. The limitation of reading materials was overcome by increasing the madrasah budget allocation to increase the collection of storybooks and learning texts. Barriers to the decline in student motivation are overcome by giving awards to students.